Iceafe1, an Actively Excising Genetic Element from the Biomining Bacterium Acidithiobacillus Ferrooxidans - Levican-Jaque, G (2013)
Integrative conjugative elements (ICEs) are self-transferred mobile genetic elements that contribute to horizontal gene transfer. An ICE (ICEAfe1) was identified in the genome of Acidithiobacillus ferrooxidans ATCC 23270. Excision of the element and expression of relevant genes under normal and DNA-damaging growth conditions was analyzed. Bioinformatic tools and DNA amplification methods were used to identify and to assess the excision and expression of genes related to the mobility of the element. Both basal and mitomycin C-inducible excision as well as expression and induction of the genes for integration/excision are demonstrated, suggesting that ICEAfe1 is an actively excising SOS-regulated mobile genetic element. The presence of a complete set of genes encoding self-transfer functions that are induced in response to DNA damage caused by mitomycin C additionally suggests that this element is capable of conjugative transfer to suitable recipient strains. Transfer of ICEAfe1 may provide selective advantages to other acidophiles in this ecological niche through dissemination of gene clusters expressing transfer RNAs, CRISPRs, and exopolysaccharide biosynthesis enzymes, probably by modification of translation efficiency, resistance to bacteriophage infection and biofilm formation, respectively. These data open novel avenues of research on conjugative transformation of biotechnologically relevant microorganisms recalcitrant to genetic manipulation. Copyright © 2013 S. Karger AG, Basel.
Keywords: Integrative and conjugative element; Horizontal gene transfer; Acidithiobacillus ferrooxidans